Role and Potential Mechanism of Heme Oxygenase-1 in Intestinal Ischemia-Reperfusion Injury - Kazuhiro Katada; Tomohisa Takagi; Takaya Iida; Tomohiro Ueda; Katsura Mizushima; Akifumi Fukui; Tetsuya Okayama; Kazuhiro Kamada; Kazuhiko Uchiyama; Takeshi Ishikawa; Yuji Naito; Yoshito Itoh (MDPI AG, 2022)
Intestinal ischemia-reperfusion (IR) injury is a complex, multifactorial, and pathophysiological condition with high morbidity and mortality, leading to serious difficulties in treatment, especially in humans. Heme oxygenase (HO) is the rate-limiting enzyme involved in heme catabolism. HO-1 (an inducible form) confers cytoprotection by inhibiting inflammation and oxidation. Furthermore, nuclear factor-erythroid 2-related factor 2 (Nrf2) positively regulates HO-1 transcription, whereas BTB and CNC homolog 1 (Bach1) competes with Nrf2 and represses its transcription. We investigated the role and potential mechanism of action of HO-1 in intestinal IR injury. Intestinal ischemia was induced for 45 min followed by 4 h of reperfusion in wild-type, Bach1-deficient, and Nrf2-deficient mice, and a carbon monoxide (CO)-releasing molecule (CORM)-3 was administered. An increase in inflammatory marker levels, nuclear factor-κB (NF-κB) activation, and morphological impairments were observed in the IR-induced intestines of wild-type mice. These inflammatory changes were significantly attenuated in Bach1-deficient mice or those treated with CORM-3, and significantly exacerbated in Nrf2-deficient mice. Treatment with an HO-1 inhibitor reversed this attenuation in IR-induced Bach1-deficient mice. Bach1 deficiency and treatment with CORM-3 resulted in the downregulation of NF-κB activation and suppression of adhesion molecules. Together, Bach1, Nrf2, and CO are valuable therapeutic targets for intestinal IR injury.